Catalytic oxidation of formaldehyde over CeO2-Co3O4 catalysts - 卢素红 王凡 陈参昌 黄风林 李克伦 (Journal of rare earths, 2017)
A series of CeO2-Co3O4 mixed oxide catalysts with different Co/（Co＋Ce） atomic ratios were synthesized by citric acid sol-gel method and used for catalytic oxidation of formaldehyde（HCHO）. Many techniques such as Brumauer-Emmett-Teller（BET）, X-ray diffraction（XRD）, scanning electron microscopy（FE-SEM）, temperature programmed reduction（H_2-TPR）, temperature-programmed desorption（O_2-TPD） and X-ray photoelectron spectroscopy（XPS） were used to characterize catalysts. The results of catalytic performance tests showed that the catalyst CeO_2-Co_3O_4 with Co/（Co＋Ce） ratio of 0.95 exhibited the best performance, and the temperature of complete oxidation of HCHO was 80 oC. The analytical results indicated that the addition of CeO_2 enhanced the specific surface area of Co_3O_4 and the fine dispersion of both of them. Moreover, the strong interaction between CeO_2 and Co_3O_4 resulted in the unique redox properties, which enhanced the available surface active oxygen and led to high valence state of cobalt oxide species. All those effects played crucial roles in the excellent performance of CeO_2-Co_3O_4 for the HCHO oxidation.